Among‐individual behavioral responses to predation risk are invariant within two species of freshwater snails. (8th February 2023) - Toscano, Benjamin J.; Allegue, Hassen; Gownaris, Natasha J.; Drausnik, Marta; Yung, Zach; Bauloye, Daniel; Gorman, Flynn; Ver Pault, Mia
Abstract: Prey behavioral response to predation risk drives a range of ecological and evolutionary processes. Key to these effects is the degree to which conspecifics exhibit consistent individual differences in their response to risk or instead follow a mean population‐level pattern. Here, we employed the behavioral reaction norm framework to quantify among‐individual variation in average predator avoidance behavior (i.e., behavioral types) and the behavioral response to risk (i.e., individual plasticity) in two snail species ( Helisoma trivolvis and Physa acuta ) that differ in their vulnerability to predators. While both snail species exhibited substantial variation in behavioral types, individual plasticity in response to risk was remarkably invariant—both snail species increased avoidance behavior with increasing risk, but all conspecific individuals followed the population‐level pattern (i.e., parallel reaction norms). Instead, individual snails differed in how they adjusted their behavior over the course of repeated behavioral assays ( n  = 12 per individual), with some exhibiting increased sensitization to risk cues and others habituation. We further show that among‐individual behavioral variation, both in behavioral types and in individual responses to repeated assays, was sometimes correlated with physiological traits, providing potential mechanisms for the maintenance of this variation. In total, our results indicate that behavioral types and individual plasticity vary at different hierarchical scales (individual‐ vs. population‐level, respectively) in freshwater snails, which has implications for species interactions and the evolution of predator avoidance behavior. Abstract : Whether or not conspecific individuals exhibit persistent differences in their behavioral response to predation risk is important for understanding the ecology and evolution of predator–prey interactions. Using two snail species that differ in their vulnerability to predation, we show that individual snails vary substantially in their mean predator avoidance but are indistinguishable in their response to risk. Our work suggests that behavioral types and individual plasticity are under different forms of selection in freshwater snails.